2019
DOI: 10.1001/jamapsychiatry.2018.3546
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Mobile Monitoring of the Dynamic Associations Among Motor Activity, Energy, Mood, and Sleep in Adults With Bipolar Disorder

Abstract: IMPORTANCE Biologic systems involved in the regulation of motor activity are intricately linked with other homeostatic systems such as sleep, feeding behavior, energy, and mood. Mobile monitoring technology (eg, actigraphy and ecological momentary assessment devices) allows the assessment of these multiple systems in real time. However, most clinical studies of mental disorders that use mobile devices have not focused on the dynamic associations between these systems. OBJECTIVES To examine the directional asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 90 publications
4
140
0
Order By: Relevance
“…The centrality of symptoms related to activation (eg fatigue and motor hyperactivity) suggests that intervening specifically on these symptoms would also be effective and efficient in treating bipolar illness. Recent work has found that increased motor activity, but not mood, predicts circadian and sleep dysregulation within bipolar disorder, suggesting that intervening on motor activity and energy may be more efficacious for these symptoms than targeting mood . Preliminary findings suggest that behavioral interventions for the management of sleep and insomnia—which often address levels of daily or nightly activation—reduce rates of bipolar relapse and improve general functioning .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The centrality of symptoms related to activation (eg fatigue and motor hyperactivity) suggests that intervening specifically on these symptoms would also be effective and efficient in treating bipolar illness. Recent work has found that increased motor activity, but not mood, predicts circadian and sleep dysregulation within bipolar disorder, suggesting that intervening on motor activity and energy may be more efficacious for these symptoms than targeting mood . Preliminary findings suggest that behavioral interventions for the management of sleep and insomnia—which often address levels of daily or nightly activation—reduce rates of bipolar relapse and improve general functioning .…”
Section: Discussionmentioning
confidence: 96%
“…Recent work has found that increased motor activity, but not mood, predicts circadian and sleep dysregulation within bipolar disorder, suggesting that intervening on motor activity and energy may be more efficacious for these symptoms than targeting mood. 57 Preliminary findings suggest that behavioral interventions for the management of sleep and insomnia-which often address levels of daily or nightly activation-reduce rates of bipolar relapse and improve general functioning. 58,59 Behavioral activation has large effects on anhedonia and fatigue, in addition to depressed mood 60 ;…”
Section: Discussionmentioning
confidence: 98%
“…Recent developments in wearables technology make them suitable for healthcare purposes. Mobile health technology has been explored in different diseases and patient groups [6][7][8][9] and the use of wearables including smartphones and sensor-equipped devices in medical research is growing constantly. There is research activity in cancer patients using activity monitors, consisting mostly of a pedometer or accelerometer [10].…”
Section: Introductionmentioning
confidence: 99%
“…We used SOLAR to estimate heritability of traits by creating a pedigree structure of MZ and DZ twin families, and we considered three possible covariates, sex, age and body mass index (BMI), given their known influence on sleep/wake and circadian traits. [30][31][32][33] The SOLAR "polygenic" command performs a variance component analysis to determine broad sense heritability.…”
Section: Discussionmentioning
confidence: 99%
“…The SOLAR software package https://helix.nih.gov/Documentation/solar-6.6.2-doc/03.chapter.html provides extensive capabilities for analyzing heritability and has been widely used in family and twin studies. We used SOLAR to estimate heritability of traits by creating a pedigree structure of MZ and DZ twin families, and we considered three possible covariates, sex, age and body mass index (BMI), given their known influence on sleep/wake and circadian traits . The SOLAR “polygenic” command performs a variance component analysis to determine broad sense heritability.…”
Section: Methodsmentioning
confidence: 99%